MENYIBAK KETABUAN: SEBUAH TINJAUAN ATAS SOCIAL MARKETING PROGRAM PENCEGAHAN HIV-AIDS DI INDONESIA - Yera Ameilia (Universitas Trunojoyo Madura, 2015)
HIV-AIDS cases has been increasing around the world and became one of the worrying problem faced by most parts of the world. Social marketing be one way that can be done to reach social objectives in influencing people's behavior, including HIV-AIDS prevention. Social marketing programs can be applied for the prevention of HIV-AIDS, but social marketing of condoms be an effective way in preventing HIV-AIDS. Social marketing of condoms has been effectively implemented by various countries to raise public awareness of used the condoms in preventing the transmission of HIV-AIDS, but the application of a condom social marketing program regarded taboo and supported with various problems in the society. It makes Indonesian people lack awareness about condoms and do not understand that the actual use of condoms is very important in the prevention of HIV-AIDS.